Lembaga Keuangan Syariah di Aceh: Tantangan dan Peluang - Farma, Junia; Umuri, Khairil (AT-TASYRI': JURNAL ILMIAH PRODI MUAMALAH, 2024)
Aceh is a region that applies Islamic law, including in the economic sector. Every sharia financial institution in Aceh must operate in accordance with Islamic law, therefore, sharia financial institutions in Aceh face several challenges and opportunities. This research analyzes the challenges and opportunities faced by Islamic financial institutions in Aceh. This research uses a qualitative approach with descriptive analysis methods. Data collection was carried out by interviewing several informants consisting of OJK Aceh, Academics, and DSN-MUI. The research results show that there are several challenges faced by sharia financial institutions in Aceh, such as a lack of quality Human Resources (HR), the existence of sharia financial institutions in Aceh is still limited, a lack of investors in sharia financial institutions, and the Financing to Deposit Ratio (FDR) Sharia financial institutions in Aceh are still low compared to the national average. Apart from the challenges above, Islamic financial institutions also have opportunities such as top-down regulation of Islamic financial institutions providing legal certainty and full support from the government, and the market potential for Islamic financial institutions in Aceh is very large because the majority of the population is Muslim. Therefore, Islamic financial institutions in Aceh must adapt sharia-based strategies to overcome challenges and take advantage of existing opportunities.